Peningkatan Manajemen Keuangan Dan Strategi Pemasaran Dalam Meningkatkan Pendapatan Nelayan Sangrawayang Kec. Simpenan Sukabumi - Wira Wibawa, Herry; Murti, Wahyu; Ratnasih, Cicih; Muhammad Ali, Hendry; Utami, Putri; Widya Ningsih, Mutiara (Jurnal Pengabdian Masyarakat Ekonomi, Manajemen dan Akuntansi (JPMEMA), 2023)
The majority of people in Sangrawawayang village, Simpenan subdistrict, Sukabumi Regency, make their living as fishermen. Community service is a process of providing services for the benefit of the community. Preparation for implementing community service begins with planning activities or observations and continues with communication and coordination. Create an activity schedule with a specific time and location at the fishing beach in Sangrawayang Village, Simpenan District, Sukabumi Regency, with the goal of inspiring the local fishermen to manage their finances and market their fish, which are typically sold for a reasonable price. The management of funding sources began to make good and correct bookkeeping so that you can know the income you have earned and also have the ability to separate the initial capital from the profits so that you can carry out processing again without collecting the funds again. Community service activities were conducted in the fishing village of Sangrawayang Village, Simpenan District, Sukabumi Regency, from October 23, 2023, to October 28, 2023. The outcomes of fish processing and marketing techniques when fish is processed and wrapped in branded plastic. Fisherwomen started to keep track of the sources of good funds that came in and went out as they started to comprehend the bookkeeping and fund management procedures. Utilizing the most recent advancements in science and technology, the problem of funding sources can be resolved. Salted fish can be processed by choosing and sorting the fish, and the finished product can be packaged beautifully and marketed more effectively.